Asymptotics of the solution of parabolic problems with nonsmooth boundary functions - Omuraliev, Asan; Abylaeva, Ella (Eurasian Mathematical Journal, 2024)
In this paper, we construct the asymptotics of the solution to a singularly perturbed parabolic problem with a nonsmooth boundary layer function. In contrast to works devoted to this direction, our asymptotics contains only one boundary layer function, which is the product of parabolic and exponential boundary layer functions. Our approach allows us to construct a classical solution without applying smoothing procedures